PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BOARD GAME “GUESS THE NUMBER” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Rifda Nurafifah; Isna Rafianti; Nurul Anriani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The aim of this research is to produce a valid, practical, and effective learning media in the form of a board game to enhance students' critical thinking skills. The research uses the 4D model, consisting of the define, design, development, and disseminate stages. It was conducted in one of the middle school in Serang, involving seventh-grade students (one class). The result of this research and development is a learning board game named "Guess the Number," which is considered valid, practical, and effective to improving students' critical thinking skills. The validity of the media is confirmed by teachers and lecturers, with a media validity percentage of 83.3% and material validity of 95%. The practicality of the media is confirmed by teachers and students, with a percentage of 86.8%. The effectiveness of the media, based on the n-gain score, is 0.682, with a percentage of 68,2% which was in the medium category with an effective interpretation